Faktor Penyebab Kegagalan Kontraktor dalam Proses Tender di Kalimantan Timur - Cindy Orvala; Habir Habir; Findia Findia (Universitas Batanghari Jambi, 2026)
The tender process is a crucial stage in the procurement of government construction projects because it plays a role in determining competent and capable contractors. However, in its implementation, many contractors still experience failure in the tender process, especially in construction projects in East Kalimantan. This condition indicates the existence of various factors that need to be analyzed systematically. This study aims to identify the dominant factors that cause contractors to fail in participating in the tender process of construction projects. The research method used is a descriptive approach by collecting primary data through questionnaires to contractors as respondents. Data were analyzed using validity tests, reliability tests and frequency analysis based on the average value (mean). The results of the study show that contractor failure is influenced by four main aspects, namely administrative aspects, technical aspects, price aspects and other aspects, with dominance in administrative and technical aspects. The results of this study emphasize the importance for contractors to improve work through more planned, systematic, and appropriate administrative and technical planning management in accordance with the provisions of the procurement documents. On the other hand, the government as the procurement organizer needs to improve guidance, socialization and evaluation of the fulfillment of administrative and technical requirements so that the tender implementation can take place effectively, efficiently, transparently and support the improvement of the quality of construction project implementation.